تأثير الاحتراق الوظيفي في أداء العاملين بحث ميداني في مؤسسة الاسمنت عين التوتة الوحدة التجارية تقرت - سليم, بن زهرة; توفيق, بوخلوه (University of eloued جامعة الوادي, 2020)
"هدفت الدراسة إلى معرفة تأثير الاحتراق الوظيفي في أداء العاملين، وتم إسقاطها ميدانيا على مؤسسة الإسمنت عين التوتة الوحدة التجارية تقرت، وقد اشتملت الدراسة على متغير مستقل تمثل في الاحتراق الوظيفي، ومتغير تابع تمثل في أداء العاملين، وذلك من خلال البحث في العلاقة بين الاحتراق الوظيفي وأداء العاملين، وهل توجد فروق في مستويات الاحتراق الوظيفي تعزى للمتغيرات الديمغرافية، واعتمدت الدراسة على المنهج الوصفي التحليلي،حيث بلغت عينة الدراسة (51) عامل، ولتحقيق هدفنا تم الاستعانة بالملاحظة ووثائق المؤسسة والاستبيان كأدوات للدراسة، وتم معالجة المعلومات، بواسطة البرنامج الإحصائي (spss.v20) اعتمادا على الأساليب الإحصائية. وقد كانت ابرز النتائج التي توصلنا إليها، وجود دراجات منخفضة من الاحتراق الوظيفي لدى مجمل أفراد العينة، ارتفاع أداء العاملين لدى مجمل أفراد العينة، وجود علاقة عكسية بين الاحتراق الوظيفي بأبعاده الثلاثة وأداء العاملين، عدم وجود فروق في مستويات الاحتراق الوظيفي تعزى لبعض المتغيرات الديمغرافية. هذا وقد توجت الدراسة بعدد من التوصيات قصد المحافظة على الدرجات المنخفضة للاحتراق إن أمكن وذلك للحفاظ على المستويات العالية لأداء العاملين. ""Abstract: The study aimed to know the impact of job burnout on the performance of workers, and it was field-projected on the cement establishment, Ain Al-Tuta, the commercial unit of Taqrat. And the performance of employees, and are there differences in the levels of job burnout due to demographic variables, and the study relied on the descriptive analytical approach, where the study sample reached (51) workers, and to achieve our goal, observation, institution documents and questionnaire were used as tools for the study, and the information was processed, by the statistical program (spss). .v20) depending on statistical methods. The most prominent results we reached were the presence of low cycles of job burnout among the total sample members, the high performance of workers among the total sample members, the presence of an inverse relationship between job burnout in its three dimensions and the performance of workers, and the absence of differences in job burnout levels due to some demographic variables. The study culminated in a number of recommendations in order to maintain low levels of combustion, if possible, in order to maintain high levels of employee performance. "
مذكرة ماستر اقتصاد وتسيير مؤسسات
Keywords: احتراق الوظيفي، أداء، أداء العاملين، إجهاد الانفعالي، تبلد المشاعر، نقص الانجاز الشخصي، قدرات فردية.; job burnout, performance, employee performance, emotional stress, dulling of feelings, lack of personal achievement, individual abilities